Efeito das interfaces térreas na percepção dos usuários em passeios públicos - Pontes, Carlos Filipe da Silva (2023)
Ground floor interfaces - the set of facades and other vertical and horizontal elements, within the pedestrian's field of vision – are fundamental to the quality of an urban space, contributing to the interaction between the public and the building, security and urban vitality. Whit that in mind, this study seeks to clarify which physical elements of ground floor interfaces are most attractive to users and what their effects are on users’ perceptions and impressions. The investigation employes a two-step methodology. The first is exploratory and uses Evaluation Grid Method (EGM), a technique based on the Theory of Personal Constructs (TCP) proposed by the American psychologist George Kelly, to determine the most valued elements and relate them to the sensations and impressions aroused. Afterwards, it employes environmental simulation with 3D scenarios and semantic differential questionnaires to test the effect of those elements. Lay participants and experts evaluated a set of nine urban street environments to determine the effects of building setback, use and treatment of the facade, visual permeability and state of facade conservation on users’ perception across 15 evaluation scales. Finally, the data was analyzed using statistical methods of analysis of variance (ANOVA). The results indicate the influence of all factors, with the conservation status having the broadest and most intense effect. In general, people are attracted to environments with greater spatial amplitude, commercial and institutional uses, visual permeability between 45% and 75% and that are well maintained. The findings can help designers and urban designers to make decisions that create more attractive and pleasant public spaces, contributing to increase the occupancy and vitality of cities.